Geomechanical Behavior Of Banded Limestone And Sandstone Formations In The Kurnool Sub-Basin: Implications For Underground Excavation Stability (International Journal of Environmental Sciences, 2025)
The Kurnool Sub-basin, a part of the Proterozoic Cuddapah Supergroup in southern India, hosts extensive exposures of banded limestone and quartzitic sandstone formations. These lithologies are increasingly targeted for underground excavations associated with hydropower tunnels, mining operations, and strategic subsurface facilities. However, their complex fabric and anisotropic geomechanical response present challenges in excavation stability and support design. This study presents a comprehensive investigation into the geomechanical behavior of banded limestone and sandstone formations from the Kurnool Sub-basin. A combined approach using field mapping, laboratory testing (uniaxial compressive strength, Brazilian tensile strength, P-wave velocity, point load test, and triaxial shear strength), petrographic analysis, and numerical modeling (using FLAC3D) was adopted.The results show that banded limestones exhibit significant heterogeneity in strength parameters, with UCS values ranging from 38–74 MPa and tensile strength from 3.2–7.8 MPa. In contrast, quartzitic sandstones exhibit more consistent behavior with UCS in the range of 88–115 MPa and high P-wave velocities (>5.0 km/s), indicating superior stiffness. SEM and thin-section studies reveal alternating micrite and sparite bands in limestone and intergranular quartz bonding in sandstone, accounting for the contrasting behaviors. The FLAC3D model simulations indicate increased deformation and shear zone development along banded planes in limestone under typical tunnel excavation stresses.The study concludes that anisotropy in banded limestone significantly reduces its deformation resistance and increases the risk of shear failure during excavation. Appropriate support measures, orientation-controlled excavation, and anisotropy modeling are essential to ensure long-term stability.